Students’ Reading Interest in Eleventh Grade of SMA Lab Undiksha Singaraja - Ellyani, Putu Rossa (Journal of Educational Study, 2023)
Reading has a very important social role in human life. Reading enriches knowledge. The more you read, the wider your thinking horizon. First, reading is a means of communication, in a cultured society. Second, the readings produced are mostly from a person’s social background. Third, as long as reading, the results of the reading will be recorded. Activities in the teaching and learning process are also inseparable from reading activities, such as in repeating a subject matter given by the teacher and in finding supporting materials in associating the teacher’s information. Likewise, working on questions requires reading. The problem that arises is that some students lack interest in reading in supporting reading teaching. This causes some students to lack in understanding the purpose of reading. Given how important reading is, especially for students’ education, they must learn to read to increase their own knowledge.